Entrepreneurial Digital Community: Networks to Prevent Advertising Fraud in Colombia - Cárdenas Ortiz, Luis Carlos (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The objective of this study was to examine the various ways in which digital advertising fraud manifests within the social media ecosystem in Colombia, with special attention to the experiences and strategies that content creators have developed to identify, confront, and mitigate this phenomenon, through a qualitative approach, phenomenological design, and descriptive type. The results reveal the impact of the preventive content from entrepreneurial influencers as a learning action to help consumers avoid being scammed, creating relevant communicative and preventive chains in digital interaction spaces.